Investigation of Seasonal Changes in Nitrate Contents of Soils and Irrigation Waters in Greenhouses Located in Antalya-Demre Region - SONMEZ, ILKER; KAPLAN, MUSTAFA; SONMEZ, SAHRIYE (Asian Journal of Chemistry, 2010)
This study was conducted to determine nitrate contents of soils and irrigation waters obtained from wells in greenhouses located in Antalya-Demre region and to investigate seasonal changes in nitrate contents. From 28 greenhouses, soil samples from 0-20 and 20-40 cm depths and irrigation water samples were collected in 3 different seasons. Analysis showed that average nitrate content in soils at 0-20 cm depth was 141.39 mg kg-1 and at 20-40 cm depth 108.14 mg kg-1. During the sampling periods, nitrate contents showed an increase at both depths. The average nitrate content in irrigation water samples was found to be 70.83 mg L-1 and showed seasonal changes. Nitrate present in irrigation waters provide an advantage in terms of nitrogen input in agricultural production. However, due to the fact that farmers utilize irrigation waters from wells for both drinking and irrigation purposes, some of the irrigation waters investigated cause health concern as drinking water since their nitrate contents exceed maximum level of 50 mg L-1 set by WHO. According to these finding, it is clear that the applications in the region increase ground water pollution. Therefore, it is important to know nitrate content of irrigation waters before their use.